Notarial Use of Electronic Signatures: A Comparative Study of Indonesia and South Korea - Dwi Kinasih, Klaura; Patricia Audrey Ruslijanto; Diana R.W. Napitupulu (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
The advancement of digital technology has significantly transformed notarial practices, particularly regarding the use of electronic signatures in the creation of authentic deeds. This study provides a normative legal analysis comparing the regulation of electronic signatures by notaries in Indonesia and South Korea, focusing on legal certainty, document validity, and authenticity. In Indonesia, the regulation is governed by Law Number 11 of 2008 on Electronic Information and Transactions as last amended by Law Number 1 of 2024, Government Regulation Number 71 of 2019 on the Implementation of Electronic Systems and Transactions, and the Notary Position Act (UUJN), which requires that deeds be signed in the physical presence of a notary. Meanwhile, South Korea comprehensively regulates this matter through the Electronic Signature Act (ESA) and the Notary Act, which authorizes notaries to use certified electronic signatures supported by a government-integrated digital verification system. This research employs a normative juridical approach with comparative legal analysis to examine the alignment and divergence of legal norms between the two countries, as well as their relation to the authenticity principle of deeds as stipulated in Article 1868 of the Indonesian Civil Code. The findings reveal that South Korea has fully implemented electronic signatures in notarial practice through robust legal and technological infrastructure, whereas Indonesia still faces normative conflicts among the ITE Law, the Notary Position Act, and the Civil Code. Therefore, regulatory harmonization is necessary to ensure that Indonesia's notarial system can transition toward digitalization while preserving authenticity and legal certainty.